2015
DOI: 10.1186/s12891-015-0604-4
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of the clavicle: report of a case in a rare location with consideration of surgical method

Abstract: BackgroundMost bone tumors that occur in the clavicle are malignant. A few giant cell tumors (GCTs) of the clavicle have been reported; however, the most appropriate operative method for this tumor has never been discussed.Case presentationA 54-year-old man noticed enlargement of the proximal aspect of the right clavicle. A plain X-ray revealed lytic change and ballooning of the proximal end of the right clavicle. The tumor was isointense on T1-weighted magnetic resonance images and showed a mixture of low- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The 3 clavicular lesions and 1 in scapula are interesting as the flat bones are hardly ever affected. Puri et al [10] found one clavicular lesion among the children in their material, and there are some existing case reports [15, 16]. Most of the larger materials contain none [1–3, 5].…”
Section: Discussionmentioning
confidence: 99%
“…The 3 clavicular lesions and 1 in scapula are interesting as the flat bones are hardly ever affected. Puri et al [10] found one clavicular lesion among the children in their material, and there are some existing case reports [15, 16]. Most of the larger materials contain none [1–3, 5].…”
Section: Discussionmentioning
confidence: 99%
“…GCT of the clavicle is rare with only 15 cases reported in literature in the last 40 years[ 3 4 6 7 8 9 10 11 12 13 14 15 ] [ Table 1 ]. Out of these, 7/15 were male and 8/15 were female.…”
Section: Discussionmentioning
confidence: 99%
“…Bone tumours of the clavicle are exceedingly rare with a reported frequency of less than 1% of all bone tumours [1], [2]. There is a paucity of literature focusing on these lesions with most of the published articles being case reports or small case series [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14]. Hence, the majority of physicians have limited experience in the diagnosis and treatment of these lesions.…”
Section: Introductionmentioning
confidence: 99%